Blacks Point of View of Discrimination in the Movie the Hate U Give (2018) - Irna Yustika Mokodongani; Rachmi Laya (Research Review: Jurnal Ilmiah Multidisiplin, 2022)
This study examines the blaks perspective between white and black that happened in life in the movie The Hate U Give by George Tillmen Jr 2018, by analyzing the two opposite perspective of dicrimination using the Critical Race Theory. Critical Race Theory is used to find out what is racial discrimination that occur in social life between black and white in United State, This theory is devided into four: everyday racism, material determinism, social construction, and intersectionality. However this study only focused on examining the blacks point of view toward racialism. Based on the result, it is foundout that there are some white people who doing indirectly racist act toward black people, such as prejuce, class, education, race, and so on discover by the system in United State who not makes the racial discrimination gone, but it has been cover and change indirectly way and most of white people did not realize it.